Community Participation in an Environmental Project: Residual Cooking Oils (Biocenosis, 2021)
During the 2014 – 2021 period, the Health Records Course at the State Distance University (UNED), develops the project: Adequate Management of Residual Fats for the Benefit of the Environment, Public Health and Rainwater Infrastructure in Montes de Oca Municipality. It is aimed at private and public food services that offer fried foods. As the project progresses, educational centers and the community are incorporated. The project´s objective was to provide nutritional and environmental education on the proper handling and elimination of these fats, based on the environment and health. In addition, oil collection and transformation into biodiesel was coordinated with different companies. The project aroused the interest of different social actors in the Montes de Oca community, private companies, and public institutions. Specially, the local government, the Ministry of Health and the UNED Ecological Blue Flag Program. The main achievement has been to link actions with different organizations, forming a common front for the well-being of the environment and public health.
Keywords: residual fat; frying; environment; education; public health